Bimbingan Teknis Tata Cara Rapat Anggota Tahunan Koperasi Berdasarkan Peraturan Perundang-Undangan di Koperasi Konsumen Sinergitas Lima Pilar - Sumiyati; Ita Susanti (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
This community service activity in the form of technical guidance on the procedures for the Annual Member Meeting (RAT) of the Cooperative is carried out in order to provide understanding to the management, supervisors and members of the cooperative. This technical guidance is carried out directly when the Five Pillar Synergy Consumer Cooperative implements the RAT for the 2021 Fiscal Year. This direct practical technical guidance activity is very effective, so that the management, supervisors, and members of the cooperative simultaneously gain knowledge and understanding of the procedures for -RAT cooperative according to statutory provisions